Phytochemical Screening and Antioxidant Activities of Geniotrigona thoracica Propolis Extracts Derived from Different Locations in Malaysia (Malaysian Journal of Fundamental and Applied Sciences, 2023)
Propolis, a natural resinous substance secreted by bees, has garnered considerable interest due to its diverse bioactive compounds and potential health benefits. Nevertheless, the phytochemical composition of propolis exhibits significant variation, influenced by multiple factors including geographical region, and botanical origin. These determinants exert profound effects on the distinctive properties and biological diversities of propolis. This study aimed to investigate the phytochemical composition and antioxidant activities of Geniotrigona thoracica propolis extracts collected from three apiary sites, designated as apiary A, apiary B, and apiary C, located in different regions within Selangor. The ethanolic extracts of propolis were prepared using 70% of ethanol and subjected to phytochemical screening to identify the presence of flavonoids, terpenoids, alkaloids, saponins, tannins, steroids, and cardiac glycosides, whilst the total phenolic content (TPC) and total flavonoid content (TFC) were measured using the Folin-Ciocalteu colorimetric and aluminium chloride methods, respectively. Additionally, the antioxidant activities of the propolis extracts were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and ferric-reducing antioxidant power (FRAP) assays. The phytochemical screening revealed the presence of flavonoids, terpenoids, alkaloids, saponins, tannins, steroids, and cardiac glycosides in all propolis extracts. The propolis from apiary A exhibited significantly higher TPC (302.21 ± 0.11 mg/mL GAE) and TFC values (99.08 ± 0.03 mg/mL QE) compared to apiary B and C. The results also indicated that propolis from apiary A possessed significantly higher antioxidant activities, with IC₅₀ value of DPPH at 25.27 μg/mL and FRAP value of 727.53 ± 0.09 μM Fe²+, in comparison to apiary B and C. A strong correlation was observed between TPC, TFC, and IC₅₀ of DPPH. This study highlights significant variations in the phytochemical compositions and antioxidant activities of propolis samples collected from different geographical and botanical sources. Further investigation is in progress to identify the specific phytochemical constituents responsible for these variations.
Keywords: DPPH, Ethanolic Extract Propolis, FRAP, Total Phenolic Content (TPC), and Total Flavonoid Content (TFC)